2014
DOI: 10.5812/ircmj.16461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SP6 Acupuncture Point Stimulation on Labor Pain and Duration of Labor

Abstract: Background:Acupressure has been used frequently to improve labor, manage labor pain, and shorten delivery time. However, there has been little research-based evidence to support the positive effects of acupressure in the obstetric area and obstetric nursing.Objectives:The aim of this study was to evaluate the effects of SP6 acupressure on labor pain and delivery time in primigravida women in labor.Patients and Methods:The study was conducted at the Trabzon Maternity Hospital in Turkey. Its design was a randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 17 publications
0
16
0
5
Order By: Relevance
“…Acupressure uses specific acupuncture points, however it is performed by pressure with fingers or hands without the use of needles (2) . A randomized controlled trial (RCT) (3) assessed the effects of acupressure on labour pain and labour duration of 100 labouring women. This study showed a lower pain score on the visual analogue scale (VAS) among the patients who received the therapy (p-value <0.001), as well as a shorter duration of labour (225 minutes for acupressure versus 320 minutes for control group, p-value = 0.000).…”
Section: Introductionmentioning
confidence: 99%
“…Acupressure uses specific acupuncture points, however it is performed by pressure with fingers or hands without the use of needles (2) . A randomized controlled trial (RCT) (3) assessed the effects of acupressure on labour pain and labour duration of 100 labouring women. This study showed a lower pain score on the visual analogue scale (VAS) among the patients who received the therapy (p-value <0.001), as well as a shorter duration of labour (225 minutes for acupressure versus 320 minutes for control group, p-value = 0.000).…”
Section: Introductionmentioning
confidence: 99%
“…Such complications necessitate the use of methods decreasing LP. Today, various pharmacological and non -pharmacological methods are used to reduce LP (8). There are considerable advantages in the application of non -pharmacological LP relief techniques with few side effects for both the mother and fetus and no interference with labor process (9).…”
Section: Contextmentioning
confidence: 99%
“…The additional points including Sanyinjiao (SP6) and Zusanli (ST36) with TCM properties to “invigorate the Blood,” “dissolve the Stasis,” “dispel the Wind,” and “open the meridian” were also selected in our study, when the patients were diagnosed with a TCM syndrome called Postpartum Qi Deficiency is commonly used for gynecologic, genitourinary, and emotional disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In TCM, Sanyinjiao (SP6), which can regulate the channel Qi of the liver, spleen, and kidney, is commonly used for gynecologic, genitourinary, and emotional disorders. Experimental research has shown that acupuncture on SP6 could have an effect on the contraction of the uterus and pain relief, and SP6 acupressure has been reported effective in decreasing pain and duration of labor for primigravida women in labor . Similarly, the general function of Zusanli (ST36) is strengthening deficiency conditions by harmonizing the Qi and Blood, and improving general weakness .…”
Section: Discussionmentioning
confidence: 99%